Implementasi Rehabilitasi terhadap Anak sebagai Korban Kejahatan Berbasis Seksual (Studi di Unit Layanan Terpadu Perlindungan Sosial Anak Integratif (ULT PSAI) Kabupaten Tulungagung) - Karisma Nilam Ayuandani; Hervina Puspitosari (Yustisia Tirtayasa, 2022)
Special protection of children who are victims of sexual violence according to The Statute of Child Protection Number 35 of 2014 is carried out through rehabilitation efforts. The same is also regulated in Law Number 12 of 2022 concerning the Crime of Sexual Violence which explains that rehabilitation is the victim's right to recovery efforts. By the mandate of the law, the government and also other state institutions should provide special protection for children, which encourages the Integrated Service Unit for Integrative Children's Social Protection of Tulungagung Regency. This institution has an ideal range of services for children, including services for children who are victims with response including victim rehabilitation. This study will analyze the implementation of rehabilitation by the Integrated Service Unit for Integrative Children's Social Protection of Tulungagung Regency for child victims of sexual violence and the obstacles to its implementation. The research methodology used is empirical juridical with a case study approach. The results of the study show that the implementation of rehabilitation of children who are victims of sexual violence must go through several processes first. The main and first process carried out is data collection and continued with mentoring. Rehabilitation is carried out through several stages, namely the initial approach, assessment, intervention, evaluation, formulation of conclusions, ending with termination. Obstacles in efforts to provide rehabilitation to child victims of sexual violence come from the lack of parental assistance related to recovery rights for children who are victims of sexual violence so that they consider that rehabilitation is a futile effort, the lack of facilities and infrastructure and the emergence of the COVID-19 pandemic makes the lack of reach to victims pose new challenges for social workers of the Integrated Service Unit for Integrative Children's Social Protection of Tulungagung Regency